2021
DOI: 10.3390/joitmc7010061
|View full text |Cite
|
Sign up to set email alerts
|

Intrapreneurial Fit and Misfit: Enterprising Behavior, Preferred Organizational and Open Innovation Culture

Abstract: In challenging times, the need for innovation is heightened and stems from employees who exhibit intrapreneurial characteristics. Not every corporate culture is a suitable environment for intrapreneurial behavior. This study examines the relationship between potential entrepreneurial behavior and preferred culture type. Through a principal component analysis of a sample of 1056 university students, four principal components of enterprising behavior (and roles) are found: Planning on results (project manager); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 87 publications
1
16
0
7
Order By: Relevance
“…Moreover, there is a strong association between innovativeness and firms' performance, which is also statistically significant, with the values of r = 0.917, beta = 0.199, and p < 0.05, which means that increasing or decreasing the activity of innovativeness by one unit or percent will result in an increment or decrement in the performance of the firm by 19.9%. Similar results were obtained by prior research work of several authors [90][91][92][93]. In addition to this, Luo et al [94] indicated that in today's stiff firm competition, the ability of entrepreneurs, managers, and business owners to innovate new products, processes, or marketing techniques has a great role in their enterprises' performance as they take market opportunities.…”
Section: Discussion Of Major Resultssupporting
confidence: 86%
“…Moreover, there is a strong association between innovativeness and firms' performance, which is also statistically significant, with the values of r = 0.917, beta = 0.199, and p < 0.05, which means that increasing or decreasing the activity of innovativeness by one unit or percent will result in an increment or decrement in the performance of the firm by 19.9%. Similar results were obtained by prior research work of several authors [90][91][92][93]. In addition to this, Luo et al [94] indicated that in today's stiff firm competition, the ability of entrepreneurs, managers, and business owners to innovate new products, processes, or marketing techniques has a great role in their enterprises' performance as they take market opportunities.…”
Section: Discussion Of Major Resultssupporting
confidence: 86%
“…In order to address the need for better user friendliness, the e-Commerce companies are urgently required to develop and implement openness of innovation for feature's website and applications continuously. From the perspective of References [67,68], open innovation is defined as an internal and external collaboration between the company, users (customers and sellers), and partners that can surpasses the company's capability. Moreover, taking a case study in Germany SMEs (Small Medium Enterprises) [75] and also from European SMEs [76], it is concluded that the openness of an integrated managerial system is considered as a guideline and a provenance of potential strategy to establish the open innovation.…”
Section: Discussion: E-crm E-loyalty and Open Innovationmentioning
confidence: 99%
“…In practice, open innovation is difficult, and the processes should be specific to each company [65]. Therefore, open innovation should be engrained in a company's core culture [66], where it is should be based on the collaboration, openness to the external knowhow, constantly embracing the change management, transparency, and readiness for reengineering [67,68]. Reference [69] established, in a study, that companies would be greatly beneficial from the open innovation by pursuing strategies that increase the legitimacy with the stakeholders [69].…”
Section: Open Innovationmentioning
confidence: 99%
“…Project management literature provided evidence that the literature on project success factors did not include the role of leadership style as a success factor to projects, as compared with the general management literature. The human skills of project managers were concluded as one of the most critical success factors in construction as well as other types of projects [14]. Peterson, et al elucidated the impact of leaders' psychological traits on firm's performance and found that positive psychological traits of leaders are strongly linked with firm performance [15].…”
Section: Introductionmentioning
confidence: 99%